Membedah Mekanisme Profitabilitas untuk Meningkatkan Harga Saham Properti dan Real Estat - Putri, Maharani; Sujito, Sujito; Prasetyaningtyas, Jayanti Jiwa (Fakultas Ekonomi, Universitas Semarang, 2024)
The aim of this research is to examine the influence of Return on Assets (ROA), Return on Equity (ROE), Net Profit Margin (NPM), and Earning per Share (EPS) on Share Prices (HS) and the role of EPS in organizations or companies in the construction and housing sectors. /property and real estate. The decision to select this study was based on the importance of this sector as an indicator of the country's economic health. Data was obtained from the annual financial reports of these organizations registered on the IDX from 2019 - 2021, using a purposive sampling technique. Quantitative method with a descriptive approach and path analysis to analyze data using SPSS software. The research results show that these three factors have a partial effect on share prices, with earnings per share (EPS) proven to be able to mediate the effect of return on assets (ROA) on share prices (HS). However, earnings per share (EPS) was not able to mediate the effect of return on equity (ROE) and net profit margin (NPM) on share prices (HS). These results indicate that investors in the property and real estate sector consider profitability and operational efficiency as indicators of company performance that have the potential to influence share prices. This research has several limitations, such as company coverage, the adjusted r-square value which influences share prices by 35.4%, and has not considered other factors that can mediate return on equity (ROE) and net profit margin (NPM) on share prices.